Penerapan Blended Learning pada Pembelajaran Tematik di Sekolah Dasar Daerah Aliran Sungai Kahayan Kota Palangka Raya - Roso Sugiyanto; Diplan Diplan; Mariane Tinse; Meisi Alvionita; Ana Fitria (Journal on Education, 2023)
This study aimed to determine the learning model at SDN 1 Menteng, Palangka Raya City during the COVID-19 pandemic. This study used a qualitative approach. The type of research used is descriptive. Sources of data taken from teachers, principals and documentation. Data collection methods were observation, interviews, and documentation. Test the validity of the data using Source Triangulation and Technique Triangulation. The methods of analysis were Data Reduction, Data Presentation, and Verification. The results of the study were: 1). The teacher prepared a blended learning lesson plan 2). Blended learning was carried out with a synchronous version, direct learning at school and through google meet, and the results of assignments were collected in boxes in classroom; and the asynchronous version, they used the whatsapp or google classroom application, 3). Evaluation of the application of blended learning used WhatsApp in giving questions to students then the results of student work were collected in boxes in classroom. 4). Supporting factors were the whatsapp application, google classroom, google meet and student handbooks. The inhibiting factor was the regulation of mass accumulation when collecting assignments.